Pengaruh Latihan Beban Menggunakan Metode Piramid Set Terbalik Dan Drop Set Terhadap Peningkatan Daya Tahan Otot Tungkai - Yusup Hidayatuloh; Risma Risma; Ucu Abdul Ropi; Hendra Rustiawan; Isna Daniyati Nursasih (Universitas Galuh, 2025)
This study aims to determine the effectiveness of reverse pyramid set and drop set training methods on increasing leg muscle endurance, and comparing the two to determine which method is more effective. The study used a Two-Group Pretest-Posttest experimental design, with a sample of 17 volleyball extracurricular students at SMAN 1 Rancah. The research program was conducted for 12 meetings with half squat training material according to the method of each group. The instrument used to measure leg muscle endurance is the Wall Sit Test. The results of the analysis using SPSS version 25, Paired Sample t-test showed that the reverse pyramid set method (Sig. = 0.000) and drop set (Sig. = 0.036) both provided significant improvement. However, the Independent Sample t-test results (Sig. = 0.843) showed no significant difference between the two methods. Thus, both training methods are effective and provide comparable results. This finding can be used as a reference in the preparation of physical exercise programs. Future research is recommended to involve a larger sample and additional variables for more in-depth results.